On pre-romanesque sculpture on the island of Pag, with special reference to the monuments with rustic features (Archaeologia Adriatica, 2020)
The paper tackles the issue of the pre-Romanesque monuments on the island of Pag. Although literature has paid substantial attention to certain groups of the monuments, several interesting finds have not been published and they are not well-known. This is why the paper, after considering some groups of pre-Romanesque finds, analyzes the separate, less known monuments, particularly the works with rustic features from the late 8th or early 9th centuries.
Keywords: Pag; pre-Romanesque sculpture; altar-screen arch; ciborium; plutei; rustic features